The Influence of Entrepreneurial Marketing Dimensions on the Performance of Wedding Organizers and Planners in Surabaya - Devi Mawarni (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
The wedding industry in Indonesia is growing very rapidly, including wedding organizer and planners. This industry is included in the red ocean business because of the many new business growths in this area. Excellent marketing skills are needed to stay in this business. One of them is by implementing entrepreneurial marketing. This study uses quantitative methods using SmartPLS for data processing. Research respondents were 112 employees of wedding organizers and planners in Surabaya. The sampling technique used was purposive sampling method. In this study, researchers wanted to know about the influence of entrepreneurial marketing dimensions on company performance. The dimensions examined for influence were innovation value creation, customer intimacy, and opportunity focus. The results obtained are that the dimension of value creation has a significant effect on company performance, while the dimensions of innovation, customer intimacy, and focus on opportunities have no significant effect on company performance.